Aquatic and soil CO2 emissions from forested wetlands of Congo's Cuvette Centrale - A. de Clippele; A. C. H. Jaeger; S. Baumgartner; S. Baumgartner; M. Bauters; P. Boeckx; C. Botefa; G. Bush; J. Carilli; T. W. Drake; C. Ekamba; G. Lompoko; et al. (Biogeosciences, 2025)
Within tropical forest ecosystems, wetlands such as swamp forests are an important interface between the terrestrial and aquatic landscape. Despite this assumed importance, there is a paucity of carbon flux data from wetlands in tropical Africa. Therefore, the magnitude and source of carbon dioxide (CO2) fluxes, carbon isotopic ratios, and environmental conditions were measured for 3 years between 2019 and 2022 in a seasonally flooded forest and a perennially flooded forest in the Cuvette Centrale of the Congo Basin. The mean surface fluxes for the seasonally flooded site and the perennially flooded site were 2.36±0.51 and 4.38±0.64 µmol<mspace width="0.125em" linebreak="nobreak"/>m-2<mspace width="0.125em" linebreak="nobreak"/>s-1<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="64pt" height="15pt" class="svg-formula" dspmath="mathimg" md5hash="0b8c9b3f35e4050769cdae1560e696a7"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="bg-22-3011-2025-ie00001.svg" width="64pt" height="15pt" src="bg-22-3011-2025-ie00001.png"/></svg:svg>, respectively. The time series data revealed no marked seasonal pattern in CO2 fluxes. As for the environmental drivers, the fluxes at the seasonally flooded site exhibited a positive correlation with soil temperature and soil moisture. Additionally, the water level appeared to be a significant factor, demonstrating a quadratic relationship with the soil fluxes at the seasonally flooded site. δ13C values showed a progressive increase across the carbon pools, from aboveground biomass to leaf litter and then to soil organic carbon (SOC). However, there was no significant difference in δ13C enrichment between SOC and soil-respired CO2. This lack of enrichment can be attributed to either a significant contribution from the autotrophic component of soil respiration or closed system dynamics.